Effect of Mold Material on Shrinkage of Investment Casting Wax Pattern - Dedy Masnur; Harrianda Hudaya; Putri Nawangsari; Warman Fatra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
Various attempts have been made to substitute metal as the wax pattern mold material due to manufacturing costs and time-consumption. This research investigates the linear and volume shrinkage on the wax pattern of gypsum, silicone rubber, and epoxy resin as alternative materials to metal molds. A nylon master pattern was made by machining. The master pattern size was set as a reference for dimensional comparison with the cast wax pattern. Wax pattern molds were created using the master pattern, namely gypsum, silicone rubber, and epoxy resin. Paraffin wax was heated up to 55˚C in metal, then poured into each wax pattern mold. The length, radius, inlet, and outlet diameter were measured using a profile projector, then the linear shrinkage was calculated. The volume shrinkage was obtained through the sample weighing. The results show that silicone rubber has the lowest linear shrinkage of any sample in contrast to its volume shrinkage.